2003
DOI: 10.1002/chin.200341220
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and Convergent Coupling Route for the Short‐Step Synthesis of Enantiopure 2α‐ and 2β‐Alkylated 1α,25‐Dihydroxy‐19‐norvitamin D3 Analogues.

Abstract: VitaminsVitamins U 0900 Efficient and Convergent Coupling Route for the Short-Step Synthesis of Enantiopure 2α-and 2β-Alkylated 1α,25-Dihydroxy-19-norvitamin D 3 Analogues. -Key steps in the novel synthesis are the radical introduction of the 2-alkyl side chain onto thiourethanes such as (II) and the C5-C6 coupling using Julia olefination. -(YOSHIDA, A.; ONO, K.; SUHARA, Y.; SAITO, N.; TAKAYAMA, H.; KITTAKA*, A.; Synlett 2003, 8, 1175-1179; Fac. Pharm. Sci., Teikyo Univ., Sagamiko, Kanagawa 199-01, Japan; Eng.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 1 publication
0
20
0
Order By: Relevance
“…We decided to connect one of the double bonds of the target diene of MART-10/MART-11 between the C5 (A-ring) and C6 (two carbons elongated CD-ring from the 8-keto group) positions using the Julia coupling approach, and the reactions turned out to be successful ( Figure 2 ). Finally, the target products were separated using a reversed phase HPLC to obtain two diastereomers, MART-10 (2 α -form) and MART-11 (2 β -form) [ 48 ].…”
Section: Development Of the Less Calcemic 19-norvitamin D Analogsmentioning
confidence: 99%
“…We decided to connect one of the double bonds of the target diene of MART-10/MART-11 between the C5 (A-ring) and C6 (two carbons elongated CD-ring from the 8-keto group) positions using the Julia coupling approach, and the reactions turned out to be successful ( Figure 2 ). Finally, the target products were separated using a reversed phase HPLC to obtain two diastereomers, MART-10 (2 α -form) and MART-11 (2 β -form) [ 48 ].…”
Section: Development Of the Less Calcemic 19-norvitamin D Analogsmentioning
confidence: 99%
“…The diastereoselectivity based on the C2-C5-C6 axis was approximately 1:1 for 13a/13b and 2.4:1 for 13a´/13b´ . The axially epimeric mixture 13 was deprotected by 10-camphorsulfonic acid (CSA) in methanol to give the mixture of MART-10 (2a) and MART-11 (2b) , which was separated by a reversed phase HPLC [33]. The other diastereo mixture 13´ was deprotected and followed by pivaloylation of the primary hydroxy group to afford the epimeric mixture 14´ , which was separated into 14a´ and 14b´ with a reverse-phase HPLC.…”
Section: The Chemistry Of Novel Synthetic Schemes For the C2-substitumentioning
confidence: 99%
“…This compound showed a selective activity profile, combining high potency in inducing differentiation of malignant cells with very low, or no bone calcification activity [63]. Further modifications to the 19-nor A-ring were also studied, such as the deletion of one of the hydroxy groups [64,65], and the introduction of a functional group at the C2 position [66][67][68][69][70][71][72][73][74][75][76]. Recent studies revealed that 2-methylene-19-nor-(20S)-1α,25-dihydroxyvitamin D 3 (2MD, 17a) induces bone formation selectively [69].…”
Section: Simultaneous Modification At Both C2 and C10 Positions: C2 Mmentioning
confidence: 99%
“…The A-ring precursor, methyl 4-allylquinicate 21, was obtained from DeLuca's thioimidazolide [62], through radical C-C bond formation using allyltributyltin (IV) and AIBN [73]. Reduction of 21 with NaBH 4 in EtOH, and the subsequent oxidative cleavage of the resulting vicinal diol using NaIO 4 gave ketone 22 in 82% yield in two steps.…”
Section: Simultaneous Modification At Both C2 and C10 Positions: C2 Mmentioning
confidence: 99%
See 1 more Smart Citation